A survey on factors that contribute to occupational stress at SAJ Holdings (Muar) / Nor Hidayah Mansor - Mansor, Nor Hidayah (Faculty of Business and Management, 2010)
People react to Occupational stress in different ways. Some coping much better than others and suffering fewer of the harmful effects of Occupational stress. Just as stress differs as a function of the individual, it also differs as a function of one's type of occupation. Some occupations are, of course, inherently more stressful than others. All of the stress-strain-health relationships have an obvious impact on the organization and industry. In order to reduce the occupational stress, employees and management level should need to aware on the factors that may contributes to occupational stress. In this research study, there are four independent variables which also the factors that may lead to occupational stress in SAJ Holding (Muar). The four factors included workload, career development, role ambiguity and co-worker. From all four factors mentioned will then determine the most factors that contribute to occupational stress. This research study also conducted with the objective to know the level of occupational stress among SAJ Holding (Muar) employees. Descriptive method is being used rather than exploratory research design or conclusive research design. Descriptive statistics, correlation and multiple regression analysis is being used to analyze the data. Among the descriptive statistics used are frequency distribution, measures of central tendency and measures of variability. Correlation analysis is used to determine the relationship between the independent and dependent variables. The result of this research finding indicated that workload is most factors that contribute to occupational stress among the employees in SAJ Holding (Muar). Besides, the level of occupational stress in this company is at moderate level. Next, after done with correlation analysis, all four independent variables are having a significant relationship towards occupational stress. As the recommendations to this company in order to reduce the level of their occupational stress they need to restructure the work design, provide social support system, provide good recognition for staffs, and also organizational and management development.